The direct and indirect effect of event severity, social support, and optimism on stress-related growth in emerging adults. Issue 10 (26th November 2021) - Li, Ting; Wang, Su-Wei; Zhou, Jing-Jing; Ren, Qing-Zhuo; Gao, Yu-Lin
ABSTRACT: Stress-related growth (SRG) can be understood as stressful experiences that act as catalysts for positive life changes. Although less severe than typical 'trauma, ' some daily obstacles may nevertheless derail faith and intentions, produce distress, result in a demand for reflection, and provide a possibility for SRG. This study examined the direct and indirect effects of event severity, social support, and optimism on SRG among emerging adults attending college in China. A convenience sample of 365 college students, ranging from 18 to 24 years old, completed surveys on event severity, social support, optimism, and SRG. We applied structural equation modeling and bootstrapping to explore optimism in the mediation model. Results demonstrated that event severity and social support have direct and indirect effects on SRG through a partial mediation effect of optimism. The results indicate that interventions targeting optimism might be an effective approach to improving SRG among college students in China.